Theory of knowledge: the 1913 manuscript - Russell, Bertrand 1872-1970; Eames, Elisabeth Ramsden; Blackwell, Kenneth (London George Allen & Unwin, 1984)
This important work was abandoned by Russell under the impact of Wittgenstein's ideas. It was first published in 1984 and is presented here for the first time in a handy student edition. In this work Russell attempts to flesh out the sketch implicit in The Problems of Philosophy . It was conceived by Russell as his next major project after Principia Mathematica and was meant to provide the epistemological foundations for his work. Russell's subsequent difficulties in presenting his theory of knowledge, brought on by what he considered to be the devastating criticisms of Wittgenstein, led both to his abandonment of this work and to a major transformation in his thought. Theory of Knowledge gives us a picture of one of the great minds of the twentieth century at work. It is possible to see the unsolved problems left without disguise or evasion. Historically, it is invaluable to our understanding of both Russell's own thought and his relationship with Wittgenstein.